All the parables of the Bible a study and analysis of the more than 250 parables in Scripture including those of the Old Testament, as well as those of our Lord and others in the New Testament - Lockyer, Herbert, 1886- (Grand Rapids, MI Zondervan, 1963)
Includes bibliographical references and index.
Brethren writer.
Keywords: Bible. N.T. Parables -- criticism, interpretation, etc